Neuropsychological correlates of obstructive sleep apnea severity in patients with epilepsy. Issue 1 (27th March 2019) - Latreille, Véronique; Willment, Kim C.; Sarkis, Rani A.; Pavlova, Milena
ABSTRACT: Aims . Obstructive sleep apnea affects up to 30% of patients with epilepsy. As obstructive sleep apnea represents a clinical risk factor for cognitive deficits, its occurrence in epilepsy patients may exacerbate cognitive deficits associated with this condition. However, the cognitive burden of obstructive sleep apnea in epilepsy remains poorly understood. We conducted a retrospective record review of adults with epilepsy who underwent a polysomnography and a neuropsychological assessment at Brigham and Women's Hospital. Methods . We examined the relationship between obstructive sleep apnea severity and cognitive functioning, particularly attention/executive functions, memory, and processing speed in untreated obstructive sleep apnea patients with epilepsy. Twenty patients with epilepsy and mild‐to‐severe obstructive sleep apnea were included in the analyses. Results . We found significant positive correlations between the oxygen saturation levels during rapid‐eye‐movement sleep and attention/executive tests ( p <0.05), as well as time spent with saturation levels ≤90% and executive functioning ( p =0.008). Similarly, worse verbal memory performances were associated with lower oxygen levels ( p =0.003). In addition, more severe respiratory events during rapid‐eye‐movement sleep were associated with worse performances on attention tests ( p =0.03). Conclusions . Our findings indicate that more severe obstructive sleep apnea‐related hypoxemia during sleep is associated with poorer cognitive performances on tests that assess attention/executive functions and verbal memory in patients with epilepsy. Overall, these results are consistent with the sleep apnea literature, and suggest that patients with epilepsy are also vulnerable to the effects of obstructive sleep apnea. Future prospective studies will help in determining whether treatment of obstructive sleep apnea may help improve cognitive functioning in patients with epilepsy.